Chronic perforated gastroduodenal ulcer: analysis of 100 observations - Leoni, Carlos; di Leoni, Francisco; Perdomo, Roberto (Cirugía del Uruguay, 1976)
A hundred cases of perforated chronic gastroduodenal ulcer are discussed. They were operated on ·b) several surgeons on the Hospital de Clínicas, of Montevideo. The most important conclusions of this analysis are reported, about the incidence, pathology, symptomatology, radiology, therapy and prognosis of this condition.